A high gain compact coplanar stripline fed antenna for wireless applications. Issue 8 (August 2014) - Roshna, T. K.; Deepak, U.; Nijas, C. M.; Sajitha, V. R.; Mohanan, P.
ABSTRACT This article proposes a novel, open stub loaded high gain, asymmetric coplanar stripline antenna for IEEE 802.11a, HIPERLAN2, HiSWANa, WiMAX (IEEE 802.11e) and ISM 5.8 application bands. The proposed antenna has an overall dimension of 24 × 23 × 1.6 mm3 when printed on a substrate of εr = 4.4 and has a 2:1 VSWR bandwidth of 23% at 5.35 GHz. The antenna exhibits a peak gain of 5.20 dBi at 5.35 GHz and a good omnidirectional radiation with an efficiency of 84%, which are validated by measurements. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:1822–1826, 2014